Integration of the PERMA Model in Physical Education Instruction to Support the Comprehensive Growth of Senior High School Students - Pureza, Faith Majella Therese A.; Ofrin, Darwin D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Physical education (PE) plays a vital role in school life as it promotes the overall development of students by addressing their emotional, social, and psychological needs along with students’ physical fitness. It is critical for Senior High School students in managing social pressures, academic expectations, and the transition to adulthood. This applies that the PERMA model, which emphasizes positive emotions, engagement, relationships, meaning, and accomplishment, explore the use in teaching Physical Education (PE) towards the holistic development such as social, emotional, physical, cognitive, and lifelong values of St. Joseph Academy of Sariaya, Quezon Grade 11 Senior High School students. A quantitative correlational research design was used to explore the relationship of PERMA in PE and the students’ holistic development. It was found that students are generally viewing themselves as functioning at a “normal” level across all PERMA components of well-being. All the five components of PERMA were identified as significant correlates of all five domains of students' holistic development, and so as the Meaning and Accomplishment component, shown as the strongest correlation among the components of PERMA model. Therefore, the researchers recommend that the Senior High School Physical Education curriculum may incorporate the PERMA model and may be more focused on integrating Meaning and Accomplishment as aspects of holistic development.